2006
DOI: 10.1093/ndt/gfl419
|View full text |Cite
|
Sign up to set email alerts
|

Weekly low-dose treatment with intravenous iron sucrose maintains iron status and decreases epoetin requirement in iron-replete haemodialysis patients

Abstract: Background. Haemodialysis patients need sustained treatment with intravenous iron because iron deficiency limits the efficacy of recombinant human epoetin therapy in these patients. However, the optimal intravenous iron maintenance dose has not been established yet. Methods. We performed a prospective multicentre clinical trial in iron-replete haemodialysis patients to evaluate the efficacy of weekly low-dose (50 mg) intravenous iron sucrose administration for 6 months to maintain the iron status, and to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…1) [7,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58], representing 24 single-arm or cohort studies and 10 parallel-arm RCT; 32 studies (94%) were published in full-text articles and 2 (6%) were scientific abstracts. The characteristics of the individual studies are displayed in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1) [7,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58], representing 24 single-arm or cohort studies and 10 parallel-arm RCT; 32 studies (94%) were published in full-text articles and 2 (6%) were scientific abstracts. The characteristics of the individual studies are displayed in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Low-dose intravenous iron therapy has advantages, such as the prevention of iron overload, maintenance of stable iron stores, effective utilization of administered iron for erythropoiesis [163], and suppression of variability of Hb level [164]. It has been reported that HD patients who are treated with intravenous iron at 50 mg/ week for 6 months maintained the target Hb levels with increasing ESA doses [165]. In contrast, another report showed that even low-dose (31.25 mg/week) intravenous iron for 12 months increased serum ferritin levels to 380 ng/mL [166], suggesting that the risk of iron overload should always be taken into account.…”
Section: (2)administration Route Of Iron For Hd Patientsmentioning
confidence: 99%
“…Although parenteral iron preparations are widely used, only few published studies explore the effects of intravenous iron treatment in iron-repleted patients on HD (table 1) [9,10,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…The extent of reduction in erythropoietin dose was shown to be dependent on the type of erythropoietin and ranged from 11 to 27% [30]. …”
Section: Discussionmentioning
confidence: 99%